'Love is a Capacity': the narrative of gendered self-development in Chinese-Style Divorce. - Xiao, Hui Faye (Journal of Contemporary China, 2010)
Employing analytical tools mainly from cultural studies and feminist theories, this article examines the televisual representation of changing family values, intimate relationships and gender dynamics parallel to China's neoliberal turn. Specifically, I will offer a close reading of Chinese-Style Divorce, a mega-hit television drama, in a larger context of sociopolitical conditions and cultural trends, particularly a neoliberal market economy and the ongoing state-sponsored 'harmonious society' campaign. I intend to explore how cultural representations of divorce play a key role in projecting and channeling the desire and fantasy of a middle-class domestic culture and in articulating a discourse of domestic and psychic interiority. Tackling rampant gender-related social problems in contemporary China, this article also seeks to address the predicaments with which middle-aged post-reproductive divorced women are confronted in a transitional time.